Impacted mandibular third molar classification during COVID-19 pandemic in rsud abdoel wahab sjahranie samarinda: Cross-sectional Study - Putri, Icha Try; Pramasari, Cristiani Nadya; Samad, Syahril (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Wisdom teeth growing obliquely or also known as impaction teeth are teeth that have not erupted completely or partially erupted, due to obstruction by surrounding teeth, bone and soft tissue so that eruption cannot be described according to their anatomical position. The purpose of this study was to determine the classification of mandibular third molar impaction teeth during the COVID-19 pandemic. Methods: This study is a quantitative study with a descriptive method using the subject of medical records and panoramic x-rays at Abdoel Wahab Sjahranie Samarinda Hospital January-June 2021. Data collection is based on predetermined inclusion criteria. Data were categorized based on age, gender and Winter and Pell and Gregory classifications described in the form of tables and narratives. Results: During the COVID-19 pandemic, the most patients with the gender category were female, with the age category being 25-34 years old, and based on the distribution of third molar impaction tooth elements were class IIA Vertical. Conclusion: Clinicians can prepare equipment and materials as well as personal protective equipment in preparation for performing odontectomy during the COVID-19 pandemic.KEY WORDS: Impacted teeth, third molar, mandibular, covid-19, radiograph Klasifikasi gigi impaksi molar ketiga mandibula pada masa pandemi COVID-19 pasien di RSUD Abdoel Wahab Sjahranie: Studi Cross-sectionalABSTRAKPendahuluan: Gigi bungsu tumbuh miring atau disebut juga dengan gigi impaksi merupakan gigi yang belum erupsi seluruhnya atau erupsi sebagian, dikarenakan terhalang oleh gigi sekitar, tulang dan jaringan lunak sekitarnya sehingga erupsi tidak dapat digambarkan menurut posisi anatomisnya. Tujuan penelitian ini untuk mengetahui gambaran klasifikasi gigi impaksi molar ketiga mandibula pasien pada masa pandemi COVID-19. Metode: Penelitian ini merupakan penelitian kuantitatif dengan metode deskriptif menggunakan subjek rekam medis dan foto rontgen panoramik di RSUD Abdoel Wahab Sjahranie Samarinda januari-juni 2021. Pengambilan data berdasarkan kriteria inklusi yang telah ditentukan. Data dikelompokkan berdasarkan usia, jenis kelamin dan klasifikasi Winter dan Pell and Gregory dijabarkan dalam bentuk tabel dan narasi. Hasil: Saat masa pandemi COVID-19 pasien terbanyak dengan kategori jenis kelamin adalah perempuan, dengan kategori usia adalah usia 25-34 tahun, dan berdasarkan distribusi elemen gigi impaksi molar ketiga adalah klas IIA Vertikal. Simpulan: Klinisi dapat mempersiapkan perlengkapan alat dan bahan serta alat perlindungan diri untuk persiapan melakukan odontektomi pada masa pandemi COVID-19. KATA KUNCI: Gigi Impaksi, molar ketiga, mandibula, COVID-19, Radiograp